A multiplex PCR for detection of haemolytic aeromonas hydrophila from vegetable sources in Karnataka, India - Venkataiah, Puttalingamma; Poojary, Niveditha Sundar; Harshvardhan, Batra (Recent Research in Science and Technology, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> Aeromonas hydrophila and other aeromonads are ubiquitous organisms commonly found in majority of food matrices intended for human consumption. They cause diarrhea, septicemia and extra-intestinal infections in normal and immunocompromised patients. The aim of the present study, to develop a multiplex PCR based strategy for the detection of pathogenic Aeromonas spp. by targeting virulence-associated genes including aerolysin (aerA), cytotonic enterotoxins (alt), serine protease (Ahe 2) gene, along with a 16S rRNA gene specific to genus Aeromonas. A competitive internal amplification control (IAC) was introduced into mPCR assay to negotiate false negative results during PCR reaction. The results showed that, developed method was useful for specific detection and differentiation of pathogenic and non pathogenic strains of Aeromonas spp. mPCR method was successfully evaluated onto several spiked as well as naturally contaminated food samples originated form Karnataka, India. The sensitivity of developed method was determined as 5x10-5 CFUml−1 from experimentally spiked food and water samples. To check the practical usefulness of developed mPCR method a total of 120 vegetable samples were evaluated. Out of 120 samples, eight samples were stayed as positive for A. hydrophila contamination. Multiplex PCR results were well correlated with that off conventional culture based methods. In conclusion developed mPCR method could provide a powerful tool for detection and differentiation of pathogenic A. hydrophila from food and environmental samples. And also it could be a better alternative for time consuming conventional culture based methods for routine food analysis laboratories.